(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Chronic hepatitis B virus (HBV) infection is a major cause of liver cancer, with 296 million individuals affected worldwide. HBV is transmitted through direct contact with infected blood and bodily fluids, unprotected sex with an infected individual, use of contaminated medical or injection equipment, and vertical transmission from an infected mother to her newborn during childbirth. Healthcare workers (HCWs) are at high risk of HBV infection in the healthcare settings. The risk of unintentional exposure among the trainees is even higher than professional due to their non-experience, insufficient training, and lack of preventive knowledge. Despite the availability of effective and safe monovalent and combined vaccines against HAV and HBV, HepA and HepB are still associated with significant morbidity and mortality worldwide. This study aims to evaluate the status, knowledge, attitudes, and myths surrounding Hepatitis B vaccination among medical students in Pakistan. Methods: From March 2024 to August 2024, 180 medical students from various colleges across Pakistan participated in a cross-sectional study. A structured questionnaire was used. SPSS v.28 was used to perform descriptive statistics and chi-square tests to analyze the data. Results: Out of 180 respondents, 108 (60%) had received vaccinations, and 43 (23.9%) had received all vaccinations. The primary reasons for not being vaccinated included a busy schedule (26.6%) and a lack of awareness about vaccination programs. Knowledge gaps were prevalent; only 11.1% of female and 1.1% of male students demonstrated good knowledge. Attitudes towards vaccination varied, with 37.2% expressing a positive attitude. They found significant associations between gender and knowledge of Hepatitis B vaccination (p = 0.045). Conclusion: There is a significant need for targeted educational programs in Pakistan to improve knowledge and dispel myths about Hepatitis B vaccination among medical students, thereby enhancing vaccine uptake and protecting public health.